Anxiety of patients undergoing ct imaging in emergency department - Kakagianni, Eyaggelia; Kelesi-Stauropoulou, Martha; Dokoutsidou, Eleni; Govina, Ourania (Health & Research Journal, 2017)
Introduction: The performance of computed tomography (CT) causes anxiety and discomfort to patients and increases the overall psychological burden. Aim: The purpose of the present study was to investigate the anxiety of patients undergoing CT when entering in the Emergency Department (ED). Material and Methods: To achieve the research objectives was conducted primary research in the ED of a General Hospital of Athens. The research was based on Convenience sampling and the data collected by a self-completion questionnaire during the period May to September 2016. The study sample consisted of 150 people. The State - Trait Anxiety Inventory (STAI) was the questionnaire of this study. Results: The mean value of the current anxiety was 58.70(± 7.32), while the general anxiety was 39.77 (± 7.32), with statistically significant difference (p <0.001). The majority of patients were very anxious prior to performing the CT. In contrast, patients do not feel special stress and anxiety in their lives in general. The factors affecting the current anxiety of patients attending ED and are to undergo CT were: age, education level, marital status, previous experience, cause of examination and presence of pain. Conclusions: One of the many challenges to be faced by health professionals is the stress management of the patient prior of the CT. The organization of intervention programs will positively contribute to the stress management and outcomes of patients.